Leitura e avaliação da compreensão leitora: reflexões sobre as percepções de estudantes de ensino fundamental - COSTA, Bianca Lima (2024)
this monograph work originated from research carried out during activities developed in the discipline “Oficina de Avaliação do Ensino-aprendizagem de Língua Materna” and involved two classes of the 9th grade of two public elementary schools in the city of Capanema/Pará. The study aimed to investigate the perceptions of students about reading and its importance, as well as the evaluation of their reading comprehension. The approach adopted has a qualitative basis (PRODANOV; FREITAS, 2013) and the method used for data collection was the application of a questionnaire. As for the theoretical foundation, the study was supported by contributions from the authors Normanda Beserra (2007), Gonçalves (2010), Almeida and Cerigato (2016) and Kramer (2010). The research revealed that students perceive reading in a positive way, however, they have varied difficulties, either in not knowing how to explain what they have read, in concentrating, as well as not understanding the meanings of some words. These data provide a reflection about what is needed for better use of reading in the classroom and success in this activity.